Alternating current oxidation of Ti-6Al-4V alloy in oxalic acid for corrosion resistant surface finishing - Bandeira, Rafael Marinho; Rego, Galtiere Correa; Picone, Carlos Alberto [UNESP]; van Drunen, Julia; Correr, Wagner Rafael; Casteletti, Luiz Carlos; Spinola Machado, Sergio A.; Tremiliosi-Filho, Germano (Springer, 2020)
In this work, alternating current (AC) voltage (V-AC) is applied to Ti-6Al-4V alloy in aqueous oxalic acid dihydrate solution to grow passive oxide films. The oxide layers are formed with V-AC values in the range of 10-80 V. The resulting surface oxide layers have estimated thicknesses in the 100-500 nm range and are expected to have a two-layer structure consisting of a porous outer layer and a compact inner layer. The AC anodization process is demonstrated to have a slight effect on the surface roughness. Porous regions are observed on the films formed at lower and high AC voltages (i.e., V-AC 10-30 and 80 V). The corrosion behavior in Ringer's solution over 48 h of exposure is studied with electrochemical impedance spectroscopy. The AC anodized samples have higher impedance values than the untreated alloy by more than an order of magnitude. The oxides formed at V-AC = 40 - 70 V exhibit optimal resistance to corrosion as demonstrated by the overall impedance values, the polarization resistance values, and the capacitive behavior.
Keywords: AC anodization; Ti-6Al-4V alloy; Oxide film; Corrosion